Representasi Budaya Patriarki dalam Film Basma Karya Fatima Al- Banawi: Kajian Semiotika Roland Barthes - Naila Zakia Ramadhani; Asep Supianudin; Ihin Solihin (JP-BSI (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2026)
This study aims to analyze the representation of patriarchal culture in the film Basma by Fatima Al-Banawi using Roland Barthes' semiotic approach. Barthes' semiotic analysis divides meaning into three levels: denotation, connotation, and myth. The scope of this research covers Sylvia Walby's form of patriarchal culture and Roland Barthes' semiotic analysis of six main scenes that depict patriarchal cultural practices, both in the private and public spheres, experienced by the female characters in the film. The method used is descriptive qualitative. The data analyzed consists of visual scenes and dialogues in the film Basma that show male domination and female subordination. The results of the study show that patriarchal culture in the film Basma is represented through various forms, including control over women's bodies and choices, the objectification of women as guardians of family honor, an emphasis on domestic roles, and the authority of male dominated institutions and social status. An interesting finding from this study is that patriarchal culture is not only explicitly present through the dialogue or actions of the characters, but is also symbolically constructed through the cinematography, setting, and the way the story is constructed, which reflects the gender ideology that is still deeply rooted in Saudi Arabian society